Electric field assisted solid‐state interfacial joining of TaC‐HfC ceramics without filler. Issue 6 (11th February 2021) - Nisar, Ambreen; Dolmetsch, Tyler; Paul, Tanaji; Zhang, Cheng; Boesl, Benjamin; Agarwal, Arvind
Abstract: The application of ultra‐high‐temperature ceramics (UHTCs) demands effective ways of joining in overcoming the problems associated with the fabrication of complex‐shaped components. In this study, we choose to investigate a new method of rapidly joining pre‐sintered TaC and HfC ceramics without any filler material using the spark plasma sintering (SPS) technique. A well‐bonded TaC–HfC interface was observed with no apparent cracking and porosity at the joint. The joining mechanisms were predominantly driven by solid‐state diffusion and localized plastic deformation. The nanomechanical properties of the TaC‐HfC joint are better than the HfC while comparable to that of the TaC. High‐load indentation (up to 200 N) results suggest that the TaC–HfC interface is stronger than the parent UHTCs with no crack propagating at the interface. Upon comparison with the parent UHTCs, the damaged area and the average crack length at the interface, reduced up to ~94% and ~56%, respectively. This study shows that the SPS technique can also apply to joining other UHTCs without any filler, resulting in the new field of developing complex components for the thermal protection system (TPS).